The Problem Of Allah’s Being Seen/Ru’yatallah According To Maturidi And Qadi Abdalcabbar - ORAL, Osman (Scientific Journal of Faculty of Theology, 2020)
The problem of Allah’s being seen (ru’yatallah) is discussed in the context of tawhed and faith. The Qur'an mentions the demands of some people to see Allah and to show Allah to them from the prophets. It is said that the sense of curiosity in man’s fitness turns into the desire to see the transcendent being Allah. The knowledge of ru'yatullah prevents the analogy of Allah to the creatures (taşbih) and the incarnation (tecsim) of Allah, that is, the idolization. Most scholars say that it is not possible to see Allah with the eye in the world, and in the hereafter it will be seen in heaven as a great grace and blessing. According to Abu Mansur al-Maturidi, Allah, the victorious (Al-Aziz) and the mighty (Al-Jalil), must be seen/ru’yat, it is true, necessary, real but this will be seen without understanding (no idrak) and without exegesis (bilakeyf). Some Islamic scholars are against (ru’yatullah) the sight of Allah. They reject the view of transcendent beings for both ontological and epistemic reasons. According to the mutazilah scholar Qadi Abdaljabbar believes that the transcendent being of Allah cannot be seen in any way in the world and in the hereafter. According to Maturidi, the praise and the tanzih of Allah occurs with the proof of ru’yatullah; according to Qadi Abduljebbar, it occurs with the absence of ru’yatullah.